Development of monitoring unit for drill bit visual inspection using digital microscope - Ali, Muhammad Afizzi Mohd (Universiti Sains Malaysia, 2017)
This paper discusses the study of developing a monitoring unit for drill bit visual inspection using digital microscope. The unit is developed as to support a wear detection computer program developed to study and inspect wear and tear on cutting lips of drill bits. The unit is developed with several things being kept in mind; axial motion (x-axis, y-axis, and z-axis), camera placement and alignment, stability, material used, and fabrication method. 3D printing and mechanical assembly were practiced in the fabrication process. The monitoring unit also comes with an illumination system. This system focuses on giving optimal lighting towards cutting lips area of drill bits. The lighting was customized so it projects at the angle of 50˚, to match the drill bit of the type 140˚ that this study is focusing into. When customized this way, the reflected light shall project perpendicularly towards camera lens. What makes this special is the light that does that only are the ones reflected by the cutting lips area only. This is a favourable in making the image captured are one with cutting lips area distinguishable to other areas. The other way the illumination is customized is by connecting a potentiometer to control light intensity. Optimal light intensity is a need too, because too much lighting will only produce a distorted image that is low in quality. To make the light projects at 50˚ angle, servos are used for accuracy and customizability. The servo is controlled by programmable microcontroller for this task. At the end of the study, image with expected quality was achieved and thus the monitoring unit shall be ready for use.